The influence of a large reservoir on the reproductive activity of the white piranha, Serrasalmus brandtii (Lütken, 1875) in Southeast Brazil - Bazzoli, Nilo; Silva, Viviane Elizabeth de Souza; Marcon, Lucas; Santiago, Kleber Biana; Santos, José Enemir dos; Rizzo, Elizete (Biota Neotropica, 2019)
Abstract: In order to assess the influence of the Três Marias dam on the reproduction of the white piranha, Serrasalmus brandtii, 1569 specimens captured from June 2011 to May 2012 in three sections of the São Francisco River basin were analyzed: section 1 = Três Marias reservoir (TMR); section 2 = São Francisco River (SFR) segment immediately downstream of TMR; and section 3 = SFR segment at the confluence with the Abaeté River. Total length (TL), body weight (BW), gonadosomatic index (GSI), and gonadal maturation stages were determined for each specimen, while vitellogenic follicle diameter, and absolute (AF) and relative (RF) fecundities were also determined for females. Reproductive activity, including spawned females and spermed males, was recorded throughout the year in the three river segments. Higher frequencies of females and males at the maturing/mature stage were found in the November/December and January/February, which coincided with the period of higher temperature, rainfall, and dissolved oxygen concentration. Mean GSI and vitellogenic follicle diameter were higher in sections 1 and 3 than in section 2 (P <0.05), while AF and RF were higher in section 1 (P <0.05) than in sections 2 and 3. The results of the present study showed that S. brandtii had lower reproductive performance in section 2, probably due to thermal disturbances caused by the dam, thus confirming the influence of dams on the reproduction of fish downstream from hydroelectric plant reservoirs.